APPROACHES TO STANDARDIZATION OF STUDENTS INFORMATION AND COMMUNICATION COMPETENCE DEVELOPMENT: THE POLISH EXPERIENCE - Mariya P. Leshchenko; Larysa I. Tymchuk (Information technologies and learning tools, 2014)
In the article foreign, in particular, the Polish experience of diagnostic of students information and communication competencies is characterized. Foreign scientists focuse their modern searches on identifying students skills of using the Internet. Standards defined by Polish researchers are multifunctional and enable the determination of the cognitive, appraisal, creative and social students skills to function in the network. Structure of seven standards (literate and successful information search, critical evaluation of information, creation, transformation and presentation of information content, legal principles of creation and distribution of information content, empathy and imagemaking, security and privacy; participation in the online communities), their components and related parameters are characterized. General results of Polish scientists researches are presented.